Relations between the Grand Duchy of Lithuania and Kazan Khanate (1506–1552) - Ya.V. Pilipchuk (Золотоордынское обозрение)
This article considers the relationship between the Grand Duchy of Lithuania and Khanate of Kazan. The aim of this study is to analyze the dynamics and characteristics of the relations of the Kazan Khanate with Grand Duchy of Lithuania. Jagiellonian eastern policy is rightfully considered as one of the most important policy directions of the Polish Kings and Grand Dukes of Lithuania in the 16th century. Researchers have traditionally paid much more attention to the history of relations of the Crimean Khanate with Lithuania and Poland. Relations of the Grand Duchy of Lithuania with Kazan Khanate have been considered in the source study articles by D. Mustafina and B. Trepavlov analyzing the content of documents preserved in the Lithuanian State Archives (Lithuanian Methric). The main theme of this article is the military and political history of Eastern Europe in the first half of the 16th century. The author aims to clarify to what extent the European policy of the Kazan Khanate depended on the personalities of Sahib Giray and Safa Giray and their personal relations with Sigismund I the Old. The novelty of this study lies in the fact that the author is the first to present to the researchers’ attention a complete picture of the Kazan-Lithuanian relations rather than focusing on particular issues of relations between the individual Grand Dukes and khans. The article examines the history of the interaction of the Kazan Tatars with Lithuanians and Poles in the context of relations of Lithuania with the Russian State and Crimean Khanate. Attempts to establish an anti-Russian alliance were undertaken during the first half of the 16th century. Mohammed Amin, from the dynasty of Ulugh Muhammad, expressed interest in the establishment of the union in 1506 only by the fact that it was profitable for him. In 1516–1518, the proposals of Sigismund I the Old to make an alliance did not meet the response in Kazan. In general, the dynasty of Ulugh Muhammad was not a supporter of rapprochement with the Grand Duchy of Lithuania. The real union between the Kazan Tatars and Lithuanians became possible only during the second rule of Safa Giray in Kazan. Only once and namely in 1535–1537, the Lithuanians supported Kazan in the war against the Russians. The continuous contact between the Kazan Khanate and Grand Duchy of Lithuania was only possible when the alliance was supported by the Crimean Khanate. Mutual raids of the Cossacks of Grand Duchy of Lithuania and troops of the Tatar frontier beys were one of the main destabilizing factors in the relationship between the Jagiellonians and Girays. The Kazan embassy to the Lithuanians and Poles in 1551 found no response from Sigismund II Augustus. The Jagiellonians were not interested in an alliance with the Kazan Tatars. Only the Crimean Girays and eastern Nogays were the staunch allies of Kazan.